Results of a pooled analysis of IOERT containing multimodality treatment for locally recurrent rectal cancer: Results of 565 patients of two major treatment centres. Issue 1 (January 2017) - Holman, F.A.; Bosman, S.J.; Haddock, M.G.; Gunderson, L.L.; Kusters, M.; Nieuwenhuijzen, G.A.P.; van den Berg, H.; Nelson, H.; Rutten, H.J.
Abstract: Objective: Aim of this study is analysing the pooled results of Intra-Operative Electron beam Radiotherapy (IOERT) containing multimodality treatment of locally recurrent rectal cancer (LRRC) of two major treatment centres. Methods and materials: Five hundred sixty five patients with LRRC who underwent multimodality-treatment up to 2010 were studied. The preferred treatment was preoperative chemo-radiotherapy, surgery and IOERT. In uni- and multivariate analyses risk factors for local re-recurrence, distant metastasis free survival, relapse free survival, cancer-specific survival and overall survival were studied. Results: Two hundred fifty one patients (44%) underwent a radical (R0) resection. In patients who had no preoperative treatment the R0 resection rate was 26%, and this was 43% and 50% for patients who respectively received preoperative re-(chemo)-irradiation or full-course radiotherapy (p < 0.0001). After uni- and multivariate analysis it was found that all oncologic parameters were influenced by preoperative treatment and radicality of the resection. Patients who were re-irradiated had a similar outcome compared to patients, who were radiotherapy naive and could undergo full-course treatment, except the chance of local re-recurrence was higher for re-irradiated patients. Waiting-time between preoperative radiotherapy and IOERT was inversely correlated with the chance of local re-recurrence, and positively correlated with the chance of a R0 resection. Conclusions: R0 resection is the most important factor influencing oncologic parameters in treatment of LRRC. Preoperative (chemo)-radiotherapy increases the chance of achieving radical resections and improves oncologic outcomes. Short waiting-times between preoperative treatment and IOERT improves the effectiveness of IOERT to reduce the chance of a local re-recurrence.